(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This study examines the poetic representation of Eastern nature and landscapes in the works of George Gordon Byron. Through a detailed analysis of Byron’s Oriental tales and travel-inspired poetry, the research explores how the poet’s firsthand experiences in the East influenced his portrayal of its natural world.